Web-Based Service Complaints App Web-Based Service Complaints Application At Class II Immigration Office of Pematangsiantar - Sakti, Bima; Saragih, Rafif Aprizki; Hamdani, Riki (Journal of Computer Science and Informatics Engineering, 2022)
This web-based service complaint application is an application that is indispensable in the evaluation process of complaints on services. With the service complaint application, it is easier for agencies to evaluate and become more integrated in making quick decisions. Because so far service complaints are still done manually. For example, every applicant/community who wants to convey a service problem must write on a piece of paper. So that the solution to the above problems is to create a web-based service complaint application which later this system will store all service complaint data into a database, so that initially complaints were made manually to become computerized. This web-based service complaint application is an appropriate and desired application and can assist agencies in improving service quality, fixing something that has not been maximized so that the service complaint process becomes faster and more efficient, especially at the Class II Immigration Office of Pematangsiantar.